Denmark : Crisis Management, Bank Resolution, and Financial Sector Safety Nets: Technical Note. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2014)
This paper discusses findings and recommendations made in the Financial Sector Assessment Program Update for Denmark in the areas of crisis management, bank resolution, and financial-sector safety nets. The Danish resolution scheme has allowed the authorities to deal with mounting distress while minimizing costs for taxpayers. The scheme has enabled the orderly winding-up of the affected banks by providing for a transfer of all assets, and part of the liabilities, to the Financial Stability Company or third-party acquirers. The authorities are encouraged to further strengthen the resolution framework in line with the Bank Recovery and Resolution Directive and emerging international good practices.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet